Penelitian Literasi Digital dan Hasil Belajar pada Database Scopus (2009-2023) - Suyono .; Ardillah .; Amad Gunawan (CV. ITTC INDONESIA, 2024)
Good digital skills make it easier for students to follow any learning process. Learning outcomes are an indicator of learning success in an academic environment. The aim of this research is to explore the research landscape related to digital literacy and learning outcomes from the Scopus database. The method used is bibliographic analysis. Based on the findings, the number of publications related to digital literacy and learning outcomes increases every year from 2018 to 2022. Most documents in the United States, most documents in institutions or universities, London School of Economics and Political Science with 281 citations, 2 documents in the Journal of Information Technology Education: Research Published. , followed by the most cited paper, namely research conducted by (Falloon 2020). The second research focus is digital competence, blended learning, and technology. The third research focus is on outcomes, digital technology, and information literacy. The three research priorities above can be used as a reference for future researchers to determine research topics. The new theme keywords are digital storytelling, blended learning, artificial intelligence, technology, critical thinking, and creative problem solving.